Antibacterial evaluation of Malaysian kelulut, tualang and acacia honey against wound infecting bacteria - M. M., Aspar; Raihana Z., Edros; N. A., Hamzah (IOP Publishing, 2020)
Bacterial infection is the most common contamination on wound. Honey is one alternative plant by-product that can be used as treatment to the bacterial infection. This study aims to evaluate the antibacterial properties of Malaysian honey represented by Kelulut, Tualang and Acacia against fourteen clinically isolated bacteria strains from wound. Agar well diffusion assay was utilised to measure the diameter of inhibition zone. Determination of minimum inhibitory concentration and minimum bactericidal concentration were performed to evaluate the bacteriostatic and bactericidal effects of the honey. The antibacterial properties of Malaysian honey were compared with manuka honey (UMF 18+). Kelulut, Tualang and Acacia have the diameter of inhibition zones that ranged from 10.7 to 24.5 mm, 9.2 to 17.7 mm and no inhibition to 15.3 mm, respectively. Kelulut, Tualang and Acacia showed bacteriostatic effect against the bacteria at concentration of 50% (w/v) and below. Kelulut was the only honey that owned bactericidal effect against the fourteen bacteria while the effect was absence in Tualang and Acacia on E. coli, K. pneumonia, E. clocae and P. mirabilis. The antibacterial properties of Kelulut was comparable to manuka honey since both honey demonstrated bacteriostatic and bactericidal effects against the fourteen clinically isolated bacteria.